Diverse Farming Systems and their Impact on Macro and Microelement Content of Vegetables & Crops - Rani, Madhu; Kapoor, Sonia (Recent Advances in Food Nutrition & Agriculture, 2024)
BackgroundThe present study investigates the effect of conventional and organic farming systems on the nutritional profile of crops. Different crops, namely–millet, sorghum, sesame, mustard, fenugreek, berseem, pea, potato, and onion were cultivated through conventional agriculture in which chemical fertilizers like urea, DAP (Diammonium Phosphate) and pesticides were used and organic farming in which organic fertilizers like seaweed and vermicompost were used.ObjectiveThe experimental study was done on a field in north India from 2019 to 2021 in six different seasons, and the nutrient profile of the crops with respect to macroelements (S, K, Na, P, Ca, Mg) and microelements (B, Cu, Fe, Mn, Zn, Al) was compared.MethodsMacro and microelements were analyzed by Element analyzer and ICP-OES in both types of farming systems. The content of macro, as well as microelements, was found to be significantly higher in all the organically produced crops as compared to the conventionally grown crops.ResultsSignificant differences were observed in the macroelement content of organic onion (P- 900 mg/kg, K-2000mg/kg) and organic pea (K 2250 mg/kg) as compared to the content of conventionally grown onion (P-756 mg/kg, K- 1550 mg/kg) and pea (K-2000 mg/kg). Similarly, microelement content in the organic sesame (Fe - 3.12 mg/kg), organic millet (Fe- 2.19 mg/kg), and organic potato (Zn-200 mg/kg) was higher as compared to conventionally grown sesame (Fe 2.05 mg/kg), millet (Fe- 1.56 mg/kg) and potato (Zn 167 mg/kg).ConclusionThis investigation concludes that crops with optimum nutritional content can be produced through organic farming with minimum input and maximum production.
Keywords: Element analyzer